Barriers to the Use of Neurologic Criteria to Declare Death in Africa. (February 2022) - Lewis, Ariane; Kumpfbeck, Andrew; Liebman, Jordan; Shemie, Sam D.; Sung, Gene; Torrance, Sylvia; Greer, David
There are varying medical, legal, social, religious and philosophical perspectives about the distinction between life and death. Death can be declared using cardiopulmonary or neurologic criteria throughout much of the world. After solicitation of brain death/death by neurologic criteria (BD/DNC) protocols from contacts around the world, we found that the percentage of countries with BD/DNC protocols is much lower in Africa than other developing regions. We performed an informal review of the literature to identify barriers to declaration of BD/DNC in Africa. We found that there are numerous medical, legal, social and religious barriers to the creation of BD/DNC protocols in Africa including 1) limited number of healthcare facilities, critical care resources and clinicians with relevant expertise; 2) absence of a political and legal framework codifying death; and 3) cultural and religious perspectives that present ideological conflict with the idea of BD/DNC, in particular, and between traditional and Western medicine, in general. Because there are a number of unique barriers to the creation of BD/DNC protocols in Africa, it remains to be seen how the World Brain Death Project, which is intended to create minimum standards for BD/DNC around the world, will impact BD/DNC determination in Africa.